W poszukiwaniu hierofanii – o filmie Góra Sulejmana Jelizawiety Stiszowej - Czaja , Justyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The subject of the article is Elizaveta Stishova's film Suleiman Mountain, the action of which focuses on the Kyrgyz mountain, surrounded by religious veneration. The title place is treated as a spatial hierophany, that is, according to Mircea Eliade's concept, a place where and through which the sacred is revealed. The text will analyze the film's space-time and its symbolic dimension, and the characters' relations with the title place, especially the relationship between women and the mountain and its mythical character.